Diversity of Ethiopian Black Cumin (Nigella sativa L.) Based on Compositions of Essential Oil - Basazinew Degu; Bizuayehu Tesfaye; Wendawek Abebe; Kebebew Assefa (Biochemistry Research International)
Black cumin (Nigella sativa L.) seeds essential oil compositions (EOCs) have been used for their medicinal and aromatic values across the world since ancient times. Studies have revealed the presence of variability among black cumin genotypes in EOCs. In Ethiopia, few studies have been conducted to explore the variability of black cumin genotypes by using EOCs. This study investigated the variability of Ethiopian black cumin genotypes (EBCGs) by EOCs. Seeds of 64 N. sativa genotypes were used for this experiment. Composite samples of 100 g of seeds were collected and roughly ground from each genotype. The extraction was made by hydrodistillation using a Clevenger-type apparatus for 3 h, and the essential oil was collected by measuring the amount using a measuring pipette. The essential oil samples were stored in a refrigerator at 4°C until gas chromatography–mass spectrometry (GC-MS) analysis. Descriptive statistics was used to estimate the variations among populations’ combined mean values of EOCs using the SAS version 9.4 software package. The correlation and hierarchical clustering analysis were made based on the combined mean values of EOCs using the R-software version 4.2.2 packages. A total of 21 EOCs were detected from the essential oil of 64 EBCGs using GC-MS, out of which ρ-cymene, thymoquinone, α-thujene, carvacrol, trans-4-methoxythujane, longifolene, terpinen-4-ol, β-pinene, α-pinene, and d-limonene dominated the essential oils. Among these, ρ-cymene, thymoquinone, α-thujene, trans-4-methoxythujane, and carvacrol were the most abundant constituents in all genotypes, while the rest varied among the genotypes. It is predicted that the major EOCs will be improved by 25.33%–152.14% over improved varieties by selecting the top 5% of landraces. The abundant EOC thymoquinone had a significant and positive correlation with carvacrol and a strong and significant negative correlation with α-thujene, α-pinene, β-pinene, ρ-cymene, and d-limonene. Based on the major EOCs, cluster analysis grouped the 64 genotypes into two different chemotypes. Cluster-I: Chemotype A is characterized by a high content of thymoquinone. Cluster-II: Chemotype B is characterized by a high content of ρ-cymene. The presence of the most abundant volatile constituents in genotypes 242835, 9068, and 014_ATH means they are essential for the pharmaceutical and food industries. This study disclosed the existence of a significant diversity of EOCs among the Ethiopian N. sativa genotypes, which can be exploited for future improvement programs.